2009
DOI: 10.1063/1.3068350
|View full text |Cite
|
Sign up to set email alerts
|

Pinning control of fractional-order weighted complex networks

Abstract: In this paper, we consider the pinning control problem of fractional-order weighted complex dynamical networks. The well-studied integer-order complex networks are the special cases of the fractional-order ones. The network model considered can represent both directed and undirected weighted networks. First, based on the eigenvalue analysis and fractional-order stability theory, some local stability properties of such pinned fractional-order networks are derived and the valid stability regions are estimated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(55 citation statements)
references
References 39 publications
1
53
0
1
Order By: Relevance
“…What we have shown in this paper is that, implementing a simple pinning control scheme can effectively eliminate herding. While the idea of pinning control has been used widely to control complex networked systems [43][44][45][46][47][48][49], our contribution is to introduce it to complex resource-allocation systems. More importantly, we have developed a solid physical theory based on the mean-field approach and its variant to establish the theoretical foundation of the pinning control in such systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What we have shown in this paper is that, implementing a simple pinning control scheme can effectively eliminate herding. While the idea of pinning control has been used widely to control complex networked systems [43][44][45][46][47][48][49], our contribution is to introduce it to complex resource-allocation systems. More importantly, we have developed a solid physical theory based on the mean-field approach and its variant to establish the theoretical foundation of the pinning control in such systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our basic idea to control herd behavior is to "pin" certain agents to freeze their states so as to realize optimal resource allocation, following the general principle of pinning control of complex dynamical networks [43][44][45][46][47][48][49]. In our approach, the fraction of agents to be pinned (fixed) is ρ pin , and the fraction of unpinned or free nodes is ρ f ree = 1−ρ pin .…”
Section: B Pinning Control Schemementioning
confidence: 99%
“…And later on, Yu et al [36] concerned with pinning performance of complex dynamical network. Other research works about pinning control of complex networks can be seen in [8,12,17,22,23,24,26,30,31,32,33,34,35,40,41] and many references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the number of controlled nodes, some feedback injections have been added to a fraction of network nodes, which is known as pinning control. As a result, some researchers have focused on the investigations different pinning control strategies for various complex dynamical networks [5,8,10,14,22,23,24,25,26,29,30,31,32,33,34,35,36,39]. For example, Wang and Chen [29] revealed that, it is much more effective to pin some most-highly connected nodes than to pin randomly selected nodes since the extremely inhomogeneous connectivity distribution of scale-free networks.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In coupled chaotic oscillators, it is well-known that stability of the synchronized solution of coupled dynamical systems depends on the strength of the coupling (interaction or connection). 13,14 One of the most intuitive approach dealing with synchronization of coupled chaotic systems is to use adaptive evolving coupling, which is based on feedback information and observed in many real-world networks.…”
Section: Introductionmentioning
confidence: 99%